Analysis of Reward System, Work Facilities, and Work Discipline on the Performance of PPPA Social Service Employees of Nganjuk Regency - Setiyowati, Eni; Soedjoko, Dodi Kusuma Hadi (Universitas Nusantara PGRI Kediri, 2025)
Research purposes: To identify the influence of the Reward System, Work Facilities, and Work Discipline on employees of the Nganjuk Regency PPPA Social Service. Design/Method/Approach: This study uses a quantitative method with a causal association approach. The method is in the form of a questionnaire tested with reliability and validity tests. Using multiple linear regression analysis, and hypothesis testing (t-test, and F-test). The location of the study was at the Nganjuk Regency PPPA Social Service with the research population being all employees of the Nganjuk Regency PPPA Social Service. The sample population was 45 employees consisting of 26 ASN employees and 19 Non-ASN employees. Research Findings: In this study, the results of the T-test and F-test of each variable Reward System (X1), Work Facilities (X2), and Work Discipline (X3) have a significant effect on Employee Performance (Y). On the other hand, 0.851 means that the magnitude of the variable can explain Employee Performance by 85.1%. So there are still 14.9% other factors that still influence employee performance at the Nganjuk Regency PPPA Social Service. Theoretical Contribution/Originality: This study provides significant theoretical contributions and strengthens the literature on the findings of the influence of independent variables on dependent variables. Practitioner/Policy Implications: In practice, this research offers a solution to identify factors that influence employee performance. Research Limitations: The variables currently used do not fully influence employee performance by 85.1%, so there are still several other factors that influence employee performance so further research is needed.